Incidences of stiffness on squat jump variables - Aedo-Muñoz, E.; Bustamante-Garrido, A.; Garcés, R.; Merino-Muñoz, P.; Cerda-Kohler, H.; Rioseco, B.; Cancino-Jiménez, J.; Miarka, B.; Perez-Contreras, J.; Arancibia-Iturbe, B.; Ariagada, D. (ISBS Proceedings Archive (Michigan), 2023)
The purpose of this study was to relation level the stiffness of the patellar tendon and three portions of the Achilles tendon; inferior, middle, and superior location with performance variables in the squat jump. The sample was composed of 25 belonging to Chilean elite male handball players. It assesses stiffness tendinous patellar and Achilles tendon using to MyotonPro® device. During the squat jump assessment, two force platforms Pasco and ForceDecks® software for analysis. The main results were RFD 0-50 ms (r=0.611), RFDN 0-50 ms (r=0.550), RFD 0-100 ms (r=0.615), and RFDN 0-100 ms (r=0.624) presented a relationship with patellar stiffness, while that Achilles tendon was down relation with peak power in squat jump (r=472). This information can be useful for training judo athletes. From the results, it can be concluded that the stiffness of the patellar tendon and the Achilles tendon determine some mechanical variables of the SJ, mainly in relation to the RFD.